Musical neurofeedback for treating depression in elderly people - Ramirez, Rafael; Palencia-Lefler, Manel; Giraldo, Sergio; Vamvakousis, Zacharias (Frontiers in Neuroscience, 2015)
We introduce a new neurofeedback approach, which allows users to manipulate expressive parameters in music performances using their emotional state, and present the results of a pilot clinical experiment applying the approach to alleviate depression in elderly people. Ten adults (9 female, mean=84, SD=5.8) with normal hearing participated in the neurofeedback study consisting of 10 sessions of 15 minutes each. EEG data was acquired using the Emotiv EPOC EEG device. In all sessions, participants listened to music pieces preselected according to their music preferences, and were encouraged to increase the loudness and tempo of the pieces, based on their arousal and valence levels. Increased arousal, computed as beta to alpha activity ratio in the frontal cortex corresponded to increased loudness, and increased valence, computed as relative frontal alpha activity in the right lobe compared to the left lobe, corresponded to increased tempo. Pre and post evaluation of 6 participants was performed using the BDI depression test, showing an average improvement of 17.2% (1.3) in their BDI scores at the end of the study. In addition, an analysis of the collected EEG data of the participants showed a significant decrease of relative alpha activity in their left frontal lobe.